# how do you solve this equation correctly......5x-2(x+6)=12?

Relevance

3x - 12 = 12

3x = 24

x = 8

• it is an equation, meaning that one element is comparable to the different element. consequently, 2x + 3 equals to 7. So take 3 from the two sides. 2x = 4, right this is what occurred: 2x +3 subtract 3 and seven subtract 3. Now you have 2 accelerated by an unknown quantity which all equals 4. properly, enable's divide by 2 so as that we are in a position to isolate variable "x". 2x = 4 (2x) / 2 = 4 / 2 Then, x = 2. wish that helps!

• Anonymous

5 times a # - 2 (a # + 6) =12!!

5 times 6 -2 (4 + 6) = 12!!!

got it?

• Anonymous

5x-2(x+6)=12

5x-2x-12=12

3x-12 = 12

3x=24

x=8

• First distribute the -2

5x-2x-12=12

Add similar peices (5x-2x) and (12+12)

3x = 24

Divide boths sides by 3

x = 8

• 5x - 2x - 12 =12

3x= 24

x= 8

• 5x-2(x+6)=12

5x-2x-12=12

3x=24

x=8

hope this helps!

• Anonymous

5x-2(x+6)=12

5x-2x-12=12

3x-12 = 12

3x=24

x=8

just need understation.....hehehe...lol

• Anonymous

-6

• 5x-2(x+6)=12

5x-2x-12=12

5x-2x=24

3x=24

x=8